2018
DOI: 10.3357/amhp.4920.2018
|View full text |Cite
|
Sign up to set email alerts
|

Aviator’s Fluid Balance During Military Flight

Abstract: Overall, at 11 flights (11%) aircrew completed their flight with a meaningful fluid loss. We conclude that military flights may be associated with significant amount of fluid loss among aircrew.Levkovsky A, Abot-Barkan S, Chapnik L, Doron O, Levy Y, Heled Y, Gordon B. Aviator's fluid balance during military flight. Aerosp Med Hum Perform. 2018; 89(2):9498.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dehydration has been shown to negatively impact cognitive performance in women, even at mild levels (~1% body mass loss) (71), and may also attenuate physical performance in women in a similar pattern as seen in men (72); however, further research is needed to elucidate the practical implications of hydration as it relates to cognitive and physical performance in women. From a logistical perspective, female service members may experience voluntary dehydration due to inconvenience, modesty, and lack of appropriate gear to urinate in field settings, similar to practices used by fighter pilots during prolonged flight missions (73). Over longer missions, the effects of dehydration could become cumulative and present as a real risk to both women and men.…”
Section: Part Ii: Physiological Considerations and Environmental Stressmentioning
confidence: 99%
“…Dehydration has been shown to negatively impact cognitive performance in women, even at mild levels (~1% body mass loss) (71), and may also attenuate physical performance in women in a similar pattern as seen in men (72); however, further research is needed to elucidate the practical implications of hydration as it relates to cognitive and physical performance in women. From a logistical perspective, female service members may experience voluntary dehydration due to inconvenience, modesty, and lack of appropriate gear to urinate in field settings, similar to practices used by fighter pilots during prolonged flight missions (73). Over longer missions, the effects of dehydration could become cumulative and present as a real risk to both women and men.…”
Section: Part Ii: Physiological Considerations and Environmental Stressmentioning
confidence: 99%
“…Despite the few studies assessing hydration status during long-haul flights, some findings are available for aviators' fluid balance during military flights. Levkovsky et al [12] investigated the hydration of 48 aviators who participated in a total of 104 training flights. The authors found that their mean fluid loss rate was~465 mL/h, as evaluated by the difference in body weight [12]; nevertheless, this data should be carefully interpreted in the context of athletes traveling during a long-haul flight since the metabolic requirements and protective equipment of military aviators are far different from the resting conditions of commercial flight passengers.…”
Section: Fluid Intake During Long-haul Flightsmentioning
confidence: 99%